Energy saving lamp - Syed Mohd Hafiz, Syed Omar (2008)
In our daily life, lamp is very synonym with us. Lamp is very useful especially when in the dark environment. In the modern era, there are many types of lamp. First lamp that had been used is filament lamp. After that pendarflour lamp had been used due to the low cost and it’s brighter than filament lamp. Even, another type of lamp had been introduced, that is LED lamp. This type of lamp is having longer life span compared to filament lamp and the pendarflour lamp. Besides that, this lamp is more economical compared to the pendarflour lamp. One of the problem about this lamp, it is hard to find this type of lamp in market. Due to this, the price also expensive. In my project, I use LED as my lamp. To make my project more applicable, I used 9V rechargeable battery. Usually all the battery charger have controller to control the flow of charging process. For my project, I used op-amp as the controller. This controller will cut off the charging process when the battery achieves 9.2V. Besides that, to make the lamp more efficient, one more controller circuit had been developing. This circuit acts as the automatic switch which only will allow the lamp ON when there are no falling light on the Light Dependent Resistor, LDR. With this switching method it will make the use of the lamp is more efficient and economical.